The Effects of Mandatory CSR Disclosure on Tax Avoidance and Tax Incidence - Ding, Rui; Cao, Yuanyuan; Sun, Yanqi (Frontiers in Psychology, 2022)
The implementation of China’s mandatory CSR disclosure in 2008 provides us with a natural experiment setting. In this paper, we examine the effects of mandatory CSR disclosure on the levels of firms’ tax avoidance and tax incidence. By using a difference-in-differences model, we predict and find that mandatory CSR reporting firms tend to be less tax aggressive. Then we test who bears the burden of the effective tax rate increase. It shows that the increase of effective tax rate causes a drop in firm output and imposes a tax burden on the firms’ consumers. The reduction in output also reduces demand for the firms’ inputs and after-tax returns, passing tax burden to suppliers, other stakeholders, employees, and shareholders. In contrast, there is no evidence that the decrease of firms’ tax avoidance activities influences the tax incidence of governments, banks, and other creditors. These findings provide evidence that mandatory CSR disclosure changes firm tax planning activities and indeed influences the costs of various stakeholders.